Powerful pedagogy : teach better quicker - Powley, Ruth (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2018)
'In Powerful Pedagogy, Ruth Powley, Love Learning Ideas blogger and experienced teacher and school leader, de-bunks teaching and learning myths and shows how the more we know about pedagogy, the more able we are to make informed and efficient choices about our practice, saving ourselves valuable time. Focusing on building sequences of learning rather than one-off lessons, it is an antidote to'quick fix' books, empowering teachers as professionals in possession of'powerful' pedagogical knowledge that can be used to improve teaching in a sustainable way. Powerful Pedagogy draws extensively from a wide range of educational writers and research, offering an accessible synthesis of what really works in the classroom. Together with strategies to put theories and research into practice, each chapter contains a handy list of questions for the reflective practitioner. It explores reasons for the confusion over what constitutes effective pedagogy in recent years and presents practical research-based solutions, outlining successful and efficient: - Modelling of excellence - Explaining for understanding - Practising to fluency - Questioning as assessment - Testing to permanency - Marking for improvement - Effective planning of lessons and curriculum sequences. Powerful Pedagogy allows teachers to understand how to make the best choices about what works in the classroom, improving the quality of teaching. It is an essential companion for trainee and experienced teachers in all sectors, and for school leaders and educational trainers'--
What is powerful pedagogy? -- Four principles of effective learning -- Six principles of effective instruction -- Planning for effective instruction, part 1 : planning effective lessons -- Modelling of excellence -- Explaining for understanding -- Practising to fluency -- Questioning as assessment -- Testing to permanency -- Marking for improvement Planning for effective instruction part 2 : designing effective curriculum sequences.
Keywords: Effective teaching; Critical pedagogy